Development of Children's Literature Reading Materials to Support SDN 028228 Binjai Student Literacy Activities - Meta Melisa Br Ginting; Mutsyuhito Solin; Wisman Hadi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
This research is motivated by the lack of availability of reading materials for children's literature, reading materials that are not suitable for the age of growth and development of children's psychology, then students have an interest in reading, and reading habits are not yet entrenched, so it is necessary to develop varied reading materials and support students in activities. literacy. Children's literature reading materials are needed at SDN 028228 Binjai to support students' literacy activities. This study aims to determine the results of the development of children's literature reading materials in the form of comics to support literacy activities of SDN 028228 Binjai students. The research method used was research and development (Research and Development) by Borg and Gall. The results showed that (1) The reading material development process was carried out in several stages, namely preliminary studies, initial product development and product testing. (2) The results of the reading material feasibility test show that (a) the result of the material expert's validation on the reading material as a whole is 83.3% with the criteria of "very good". (b) the results of the validation by design experts on the reading material as a whole obtained data 88.3% with "very good" criteria. (c) the results of the overall classroom teacher assessment of the reading material obtained an average of 91% with the criteria "very good" (3) The results of the effectiveness of the development of reading materials show that (a) the results of individual trials on reading materials obtained an average of 79.6% with the criteria "good ", The results of small group trials on reading materials obtained an average of 88.2% with the criteria" very good ", limited field test results on reading materials obtained an average of 90.1% with the criteria" very good ". (b) the results of the quality of using children's literature in the form of comics to support students' literacy activities were obtained an average of 88.65% (posttest), while before the use of children's literature in the form of comics, the average was 68.40% (pretest). The difference in value is 20.25% which means that children's literature reading material in the form of comics can improve the results of students' literacy activities from before. The implications of this research are (1) children's literary reading materials to support students 'literacy activities can increase students' knowledge of North Sumatra folklore; (2) the results of this study can enrich the treasury of science in order to increase creativity in the development of reading materials, especially those related to the development of children's literature reading materials in North Sumatra.